2001
DOI: 10.1259/bjr.74.884.740752
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic vein transit time of an ultrasound contrast agent: simplified procedure using pulse inversion imaging

Abstract: The aim of this study was to ascertain whether a new ultrasound technique, namely pulse inversion imaging, could assess the arrival of a contrast agent in the hepatic veins, and to describe possible advantages of this procedure in determining transit time over a previously described method based upon spectral Doppler quantification. 15 subjects were scanned using pulse inversion imaging. A bolus injection of 2.5 g Levovist (Schering AG, Berlin, Germany) 300 mg x ml(-1) was given into an antecubital vein. Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 4 publications
2
28
2
8
Order By: Relevance
“…Using spectral Doppler imaging, Albrecht et al (1999) reported that cirrhosis was associated with an appreciably shorter hepatic vein transit time compared with controls and patients with noncirrhotic diffuse liver disease. Bang et al (2001) found that pulse-inversion imaging was a simpler and more practical technique than the spectral Doppler method in evaluating hepatic transit time in a clinical setting. However, the majority of these studies used the first-generation contrast agent (Levovist, Schering AG, Berlin, Germany) and a high mechanical index technique, in which contrast microbubbles were destroyed in the scanning plane and continuous perfusion imaging was not possible.…”
Section: Introductionmentioning
confidence: 98%
“…Using spectral Doppler imaging, Albrecht et al (1999) reported that cirrhosis was associated with an appreciably shorter hepatic vein transit time compared with controls and patients with noncirrhotic diffuse liver disease. Bang et al (2001) found that pulse-inversion imaging was a simpler and more practical technique than the spectral Doppler method in evaluating hepatic transit time in a clinical setting. However, the majority of these studies used the first-generation contrast agent (Levovist, Schering AG, Berlin, Germany) and a high mechanical index technique, in which contrast microbubbles were destroyed in the scanning plane and continuous perfusion imaging was not possible.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, some new techniques and methods have been introduced to the hemodynamic study in liver. For example, hepatic vein transit time was measured by spectral Doppler or pulse-inversion imaging [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…1). This simplified technique not only simplifies measurements of the arrival time in hepatic veins but also enables measurement of the delay between arrival in the hepatic arteries and hepatic vein which was not possible with the spectral Doppler technique [6,7]. These studies used offline P111 Fig.…”
Section: Techniquementioning
confidence: 99%